Effects of aloe vera (Aloe barbadensis Miller) gel on growth performance and haemato-biochemical profiles in broiler chickens - Islam, MM; Khalil, KKI; Islam, MA; Sujan, KM; Mustari, A; Miah, MA (Bangladesh Veterinarian, 2019)
The study was designed to assess the effects of aloe vera gel (AVG) on broiler growth performance and haemato-biochemical changes. “Lohman” day-old broiler chicks (n=48) were reared for 28 days. At day 13, chicks were randomly divided into four equal groups (12/group). Group A was non-treated control. Group B was supplemented with antibiotic (oxytetracycline hydrochloride) as a growth promoter in water. Group C and D were supplied AVG (1% and 2%) in drinking water. Antibiotic and AVG treated broilers had higher (P<0.05) live weight (1803.8 ± 63.6 gm and 1800.00 ± 64.2 gm) than control (1607.5 ± 41.7 gm). Total erythrocyte count (3.6 ± 0.1 x 106/uL), haemoglobin (9.9 ± 0.1 gm%) and packed cell volume (35.2 ± 0.4 %) were higher (P<0.05) in treated groups. It is suggested that the aloe vera gel supplementation (1-2%) may be used as an alternative to antibiotics for better growth performance in broilers without deleterious effects on haematobiochemical profiles. The Bangladesh Veterinarian (2019) 36(1 - 2): 25-32